Responsibility in the Time of Crisis - Donev, Dejan; Skalovski, Denko (NKUA Applied Philosophy Research Laboratory, Athens, Greece, 2023)
One of the crucial questions that this text seeks to answer is whether again it is just one of the current crises of the value system that we can call “western” or it is a definite end of the functioning of a particular system and its hierarchy, whose principle of growth and imperial development is predominantly determined by the economic logic of profit/capitalism and the “infinity” of its progress. The answer implies the return/internalization of positive utopian energies and a new universalist moral optimism (macro ethics) as a dialectical antipode of postmodern “liberal” antihumanism and self-destructive relativism and total nihilism. Moreover, it requires a commitment to the creation/construction of new systems of thinking and acting and great importance of the moral-political responsibility of all social subjects in those new systems of social technology.
Keywords: crises; bioethics; responsibility; life; system; subjectivity; evolution